A Workable Solution for the Pre-Medicare Population - Pamela Farley Short; Dennis G. Shea; M. Paige Powell (SAGE Publishing, 2001)
Incremental reforms to expand health coverage among older Americans are justified by medical spending that increases with age and enrollment in employer insurance that decreases with age. Older Americans are also at risk of unexpected changes in health, access to health insurance, and earnings that could leave them poorly positioned financially for their retirement years. We propose offering universal access to Medicare at a community-rated premium, with premium vouchers for those with a history of low lifetime earnings and tax-preferred savings accounts to help everyone with the increased cost of insurance at older ages. These subsidies are available for coverage obtained from sources other than Medicare. We would set the eligibility age for the buy-in at 62. However, because enrollment in employer insurance does not drop precipitously at age 62, we regard the eligibility age as an adjustable design element that could resize the program to fit political and budgetary constraints.